Integrated Omics Reveal Dendrobium nobile Lindl.’s Anti-Diabetic Mechanisms via Arginine/Proline and Glycerophospholipid Pathways - Zhibo Wang; Xian Wang; Sifan Guo; Ying Cai; Dandan Xie; Yujuan Wang; Aihua Zhang; Jun Dai; Shi Qiu (Pharmaceuticals, 2025)
Background/Objectives: Dendrobium nobile Lindl. (DNL), a traditional dietary supplement, exhibits therapeutic potential for type 2 diabetes mellitus (T2DM), yet its mechanisms remain unclear. Methods: T2DM was induced in db/db mice. DNL (10 g/kg/d) or metformin (65 mg/kg/d) was administered for 4 weeks. This study integrated pharmacodynamic evaluation and multi-omics to elucidate DNL’s anti-diabetic effects in db/db mice. Results: DNL intervention significantly ameliorated T2DM phenotypes, reducing hyperglycemia, insulin resistance, and renal dysfunction. Metabolomics analysis identified 39 differential metabolites (19 upregulated, 20 downregulated) linked to citrate cycle, oxidative phosphorylation, and glycerophospholipid metabolism, while proteomics revealed 113 differentially expressed proteins, with multi-omics integration highlighting DNL’s modulation of three proteins (Ckm, Ache, Selenbp1) and four metabolites (4-guanidinobutanoic acid, phosphorylcholine, homocysteine, succinic acid) across arginine/proline metabolism, glycerophospholipid metabolism, and sulfur metabolism. Pathway analysis demonstrated DNL’s restoration of dysregulated processes, including inflammation suppression via NF-κB and PI3K-Akt pathways, enhanced insulin sensitivity through glycerophospholipid balance, and mitigation of oxidative stress via sulfur metabolism. Key correlations between metabolites and proteins underscored DNL’s multi-target action. Conclusions: These findings systematically decode therapeutic mechanisms of Dendrobium nobile Lindl., emphasizing its role in rectifying metabolic disorders and inflammatory signaling, thereby providing a molecular basis for its clinical application in T2DM management.